Leptogenys ants (hymenoptera: formicidae; ponerinae)of Sabah - Bakhtiar , E.Y; Chiang , S.L (Pusat Sistematik Serangga ,UKM, 2010)
The study was aimed at assessment the leptogenys ants of Sabah both from the existing records and several collection sentres in Sabah. Specimens examined were from BORNEENSIS. Institute for Tropical Biology and Consevation, Universiti Malaysia Sabah; insect collection centre of forest research centre, sepilok; and entomologicalmuseum, Sabah parks. Apart from meseum specimen examination, collections were also carried out at Universiti Malaysia Sabah hill, poring hot spring, sepilok forest reserve, sapulut forest reserve, Kalabakan forest reserve and Tawau hills Park by the use of manual sampling, winkler's sampling and baited pitfall traps. A total of 797 individuals of leptogenys ants which consist of 29 species have been identified from BORNEENSIS, insect collection of forest research centre,Sepilok; and entomological museum, Sabah parks. Most of the leptogenys collections were found in BORNEENSIS (562 individuals; 21 species), followed by Sandakan (131 individuals;10 species) and Sabah parks (104 individuals; 13 species).Number of unnamed leptogenys specimens was highest in BORNEENSIS collection (10 species),followed by Sabah Parks (9 species) and Sepilok (2 species).